2021
DOI: 10.1021/acsphotonics.0c01827
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Orientation-Dependent Oxidation of Epitaxial TiN Films with Tunable Plasmonics

Abstract: Titanium nitride (TiN) is a paradigm of refractory transition metal nitrides with great potential in vast applications. Generally, the plasmonic performance of TiN can be tuned by oxidation, which was thought to be only temperature-, oxygen partial pressure-, and timedependent. Regarding the role of crystallographic orientation in the oxidation and resultant optical properties of TiN films, little is known thus far. Here we reveal that both the oxidation resistance behavior and the plasmonic performance of epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 62 publications
2
20
0
Order By: Relevance
“…Successful implementation of the titanium nitride as a plasmonic component in photonic devices has been demonstrated on the example of hyperbolic metamaterials working in the visible and infrared ranges [9,10], high-temperature-stable and irradiation-resistant broadband absorber [11], nanoantennas, or other nanostructures able to increase optical response [12][13][14][15][16][17], SERS (Surface-Enhanced Raman Spectroscopy spectroscopy) substrate [18], and remote optical temperature sensor [19]. Apart from applications, the current literature addresses issues related to optimizing the plasmonic properties [20][21][22][23][24][25][26] and the stability of the thin films [26][27][28]. Some quite modern reviews are also available [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Successful implementation of the titanium nitride as a plasmonic component in photonic devices has been demonstrated on the example of hyperbolic metamaterials working in the visible and infrared ranges [9,10], high-temperature-stable and irradiation-resistant broadband absorber [11], nanoantennas, or other nanostructures able to increase optical response [12][13][14][15][16][17], SERS (Surface-Enhanced Raman Spectroscopy spectroscopy) substrate [18], and remote optical temperature sensor [19]. Apart from applications, the current literature addresses issues related to optimizing the plasmonic properties [20][21][22][23][24][25][26] and the stability of the thin films [26][27][28]. Some quite modern reviews are also available [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to (001) and ( 110) orientations, a recent study has demonstrated that the (111)-oriented TiN is more resistant to oxidation, even under a high oxygen partial pressure at 800 °C. 42 To compare with the oxygen-free stoichiometric film grown by MBE, a sputtered (111)-oriented TiN epitaxial film is also prepared by reactive sputtering on c-plane sapphire, and the same metasurface structure is used for a direct comparison. As a simple inspection approach, the absence or presence of oxygen contamination can be judged by the film color and carrier concentration.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…As a simple inspection approach, the absence or presence of oxygen contamination can be judged by the film color and carrier concentration. 30,42 The MBE TiN film exhibits a brilliant golden color, as shown in Figure 1a, and has a free electron concentration as high as 9 × 10 22 cm −3 . 30 Furthermore, ex situ XRD measurements (Figure 1b) reveal that the full width half maxima (FWHM) of the MBE and sputtered TiN(111) peaks are 0.25°and 0.55°, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…• C for 8 h and reground for 6 h. Then the powders were pressed into a 2-inch target with 30 MPa and annealed at 1300 • C for 2 h. The high-quality NSNO 4310 thin films (∼ 20 nm) were synthesized by high-pressure radio frequency (RF) magnetron sputtering (home-made) with a 2-inch target and the O 2 (purity of 99.999%) reactive gas [43,44]. Before growth, the base vacuum pressure was ∼ 3 ×10 −8 torr.…”
Section: Methodsmentioning
confidence: 99%